2017
DOI: 10.1038/s41598-017-10689-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pressure limits of guanosine monophosphate self-assemblies

Abstract: Guanosine monophosphate, among the nucleotides, has the unique property to self-associate and form nanoscale cylinders consisting of hydrogen-bonded G-quartet disks, which are stacked on top of one another. Such self-assemblies describe not only the basic structural motif of G-quadruplexes formed by, e.g., telomeric DNA sequences, but are also interesting targets for supramolecular chemistry and nanotechnology. The G-quartet stacks serve as an excellent model to understand the fundamentals of their molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…Indeed, it has been demonstrated that this band is sensitive to the guanine structuring, since it moves from about 1693 cm −1 , found in DNA quadruplex, to 1655-1670 cm −1 , observed for single stranded DNA [35,36]. Similar results were also observed in the case of GMPNa 2 at basic pH: the self-association in quadruplexes was observed to determine a blue shift from 1657 cm −1 to 1675 cm −1 [37]. Therefore, the temperature dependence of the frequency of the C 6 =O 6 stretching modes could be a good indication for the assembling/disassembling of GMP in solution.…”
Section: R G Length From R G and R Csupporting
confidence: 69%
“…Indeed, it has been demonstrated that this band is sensitive to the guanine structuring, since it moves from about 1693 cm −1 , found in DNA quadruplex, to 1655-1670 cm −1 , observed for single stranded DNA [35,36]. Similar results were also observed in the case of GMPNa 2 at basic pH: the self-association in quadruplexes was observed to determine a blue shift from 1657 cm −1 to 1675 cm −1 [37]. Therefore, the temperature dependence of the frequency of the C 6 =O 6 stretching modes could be a good indication for the assembling/disassembling of GMP in solution.…”
Section: R G Length From R G and R Csupporting
confidence: 69%
“…This includes other Xraybased techniques (for example, smallangle Xray scattering (SAXS)) 42 , along with various microscopy techniques: atomic force microscopy (AFM) was applied to charac terize the selforganization of GMP on mica 43 , SEM was applied to investigate the folding parameters and global topology of micrometrelong Na 2 (5′GMP) assemblies 36 and scanning tunnelling microscopy (STM) was applied in combination with density functional theory (DFT) calculations to assess whether and how Gquartets can be assembled on surfaces (either Au(iii) 24,44 or highly ori ented pyrolytic graphite (HOPG) 45 surface) in solventless conditions, with simple or sophisticated guanine deriva tives, in the absence or presence of Na + , K + or Ca 2+ cations. Spectroscopic techniques provided invaluable clues about Gbased selfassemblies in solution; these include Fourier transform infrared (FTIR) 46 , infrared multiple photon dissociation (IRMPD) [47][48][49] and RAMAN 50 spectroscopies, along with electronic and vibrational circular dichroism for instance (ECD 51 and VCD 52 , respectively) combined with degenerate coupled oscillator (DCO) calculations 52 and NMR 53,54 , notably diffusionordered spectroscopy (DOSY) NMR, which were successfully implemented to characterize the cationtemplated GMP aggregation in nearphysiological conditions. Finally, theoretical mod els were provided via molecular dynamics (MD) 55,56 and molecular mechanics (MM) 57 , notably for both describ ing cationtemplated Gquartet formation and simulating in silico the movement (channelling) of cation (e.g.…”
Section: G4omementioning
confidence: 99%
“…In the past, the characterization of the self-assembled structures has been carried out exploiting nuclear magnetic resonance spectroscopy, scanning electron microscopy, dynamic light scattering, and fingerprint Raman analysis. 61 , 69 71 To the best of our knowledge, the low-frequency G-tetrad Raman response has not been reported yet and has the advantage of containing intense and easily monitored markers of tetrad formation.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the different structure and electronic distribution in oxidized nucleotides produce structural rearrangements at the intermolecular level, modifying the extent and the properties of long-range intermolecular interactions, which are reflected in the terahertz Raman response. In the past years, the characterization of the self-assembled structures has been carried out exploiting nuclear magnetic resonance spectroscopy, scanning electron microscopy, dynamic light scattering, and Raman in the fingerprint region [63,[71][72][73]. To the best of our knowledge, the low frequency Raman response of intermolecular G structures has not been reported yet and has the advantage of containing intense and easily monitored spectral markers of tetrads formation.…”
Section: Monitoring Intermolecular Organization By Terahertz Raman Sp...mentioning
confidence: 99%